The impact of paternity leave on long-term father involvement - Mari Rege; Ingeborg F. Solli (Center for Economic Studies and ifo Institute (CESifo), 2010)
Using Norwegian registry data we investigate how paternity leave affects fathers' long-term earnings. In 1993 Norway introduced a paternity quota of the paid parental leave. We estimate a difference-in-differences model which exploits differences in fathers' exposure to the paternity quota. Our analysis suggests that four weeks paternity leave during the child's first year decreases fathers' future earnings by 2.1 percent. Importantly, this effect persists up until our last point of observation when the child is five years old. The earnings effect is consistent with increased long-term father involvement, as fathers shift time and effort from market to home production. In an investigation of Norwegian time use data we find additional evidence for this hypothesis.
Keywords: D13; H31; J22; 330; father involvement; household production; parental leave; Erziehungsurlaub; Väter; Verdienstausfall; Einkommen; Zeitbudgetforschung; Norwegen